COVID-19 Vaccine Hesitancy and Social Media Use: A lesson learnt from pandemic - Tran Binh Thang; Thi Dang Thu Nguyen; Vo Nu Hong Duc; Cao Khoa Dang; Thi Thanh Nhan Tran; Duc Dan Nguyen; Hong Tram Nguyen; Minh Duy Ho; Thi Bich Thuy Le; Van Vui Tran; Van Hung Nguyen (ACHSM, 2024)
Objective: This study aims to assess the level of COVID-19 vaccine hesitancy among Vietnamese adults and examine the relationship between social media use and vaccine hesitancy. Methods: A cross-sectional study was conducted from July 26 to August 10, 2021, using an online survey of 702 Vietnamese adults. The Oxford COVID-19 vaccine hesitancy scale was used to measure vaccine hesitancy. A linear regression model was used to analyze the factors associated with vaccine hesitancy. Results: Our study found that 15.1% of respondents were hesitant about receiving the COVID-19 vaccine, with an average hesitancy score of 9.52±2.66. Students and the unemployed had higher levels of hesitancy (B=0.58; 95%CI=0.02-1.15; p=0.043 and B=1.59; 95%CI=0.41-2.76, p=0.008, respectively. Hesitancy was also significantly associated with receiving positive information from social media (Facebook, Zalo) (B=-0.31; 95%CI=0.5 to -0.12; p=0.001) and trust in social media information (B=-0.45; 95%CI=-0.72 to -0.19; p=0.001). Conclusion: The results of this study highlight the need for targeted interventions to address vaccine hesitancy among Vietnamese people, particularly in the context of the shortage of vaccines and low public trust in 2021 and its practical evidence for future preparation in emerging pandemics.